Time of Arrival Estimation of Ultra Wideband Indoor Wireless System - B. Venkata Krishnaveni, K. Suresh Reddy, P. Ramana Reddy (International Journal of Advanced Science and Technology, 2020)
The time of arrival (TOA) estimation is a very challenging task due to the high diffusive behaviour of channels in ultra wideband technology, here the first arriving signal is not consequently the efficient path. The nyquist rate sampling of UWB is difficult due to high bandwidth of UWB signal. So accurate ranging methods at lower sampling rates is needed to be designed. In this paper we are estimating TOA values using samples of the observed signal from reference nodes after calculation of energy. Performance of different time of arrival estimation algorithms are analysed using simulations for channel models of IEEE 802.15.4a standard